Colour in a new light: a spectral perspective on the quantitative genetics of carotenoid colouration. (25th June 2014) - Evans, Simon R.; Sheldon, Ben C.
Summary: Carotenoid‐based colours are model traits for research on animal signalling and sexual selection but, whereas the consequences of variable expression have been extensively studied, its causes are rarely quantified. This issue is complicated by the composite nature of carotenoid‐based colour patches, which combine pigments and a reflective background. Ultimately, the evolution of such colours will be determined by the processes that govern variable expression of these mechanisms. We present a novel approach to assessing the quantitative genetics of colour expression, in which reflectance spectra are analysed directly, thereby avoiding the data loss and inherent subjectivity of summary colour variables. Further, the influence of the component mechanisms can be distinguished in spectral analyses due to their contrasting wavelength‐dependencies. Using data from a 6‐year study of carotenoid‐based plumage reflectance in wild great tits ( Parus major ), we employ a multi‐parallel 'animal modelling' approach to estimate sources of variance for narrow (2 nm) wavebands across the visible spectrum. Moderate heritability estimates were limited to the violet‐blue region of the spectrum, diagnostic of the carotenoid content of plumage being heritable. The natal environment effect was limited entirely to the violet‐blue, again indicating that it relates to variation in carotenoid content of feathers. Other wavelengths were sensitive to annual and permanent environmental variation but only marginally influenced by additive genetic variation. Hence, background reflectance is the component that is more sensitive to the environment. Analysing reflectance spectra directly provided an objective perspective of the dynamics of colour expression that is not apparent when relying on summary colour scores. In this case, our results suggest that carotenoid deposition may be an effective target of selection and hence could explain the important role carotenoids frequently play in intraspecific signalling. Abstract : Lay Summary